Post Kolonialisme dan Perdebatan Islam Modern di Belanda - Karel Steenbrink (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2008)
Postcolonialism is not only an important issue in the cultural debate about countries that were subject to colonialism. It is quite interesting to see how the former colonial powers now look at the enduring influence of the colonial experience. Is the American aspiration to be the dominating power in the world partly a result of a lack of colonial experience? Do they not realise how difficult it is to rule over foreign nations? What is the ongoing impact of the colonial rule in the European countries? In the Netherlands the influence seems to be quite restricted. Indonesia is part of the discourse about the Dutch past, but the Dutch look at their colonial past from their own perspective. It is mostly related to the small group of people who repatriated from the former colony. This is shown in the national monuments related to the colonial past. In economic fields the colony could easily be superseded by other rela- tions. Most important is the religious issue. In the present debate about the new Muslim population in the Netherlands similar issues are important as during colonial rule. Although not often openly said, the same attitudes are shown of a very close and concerned intervention in religious affairs. A nice comparison can be made between the 6% Muslim Dutch minority in a majority Christian country and the 9% Christian Indonesian minority in an overwhelming Muslim society.